Differences of macrophages in the tumor microenvironment as an underlying key factor in glioma patients - Wang, Yangyang; Liu, Yan; Zhang, Chengkai; Zhang, Chuanbao; Guan, Xiudong; Jia, Wang (Frontiers in Immunology, 2022)
Abstract Background: Macrophages, the major immune cells in glioma microenvironment, is closely related to tumor prognosis. Further studies are needed to investigate macrophages, which will be helpful to fully understand the role of it and early achieve clinical translation. Methods: A total of 1334 glioma cases were enrolled in this study from 3 databases. In our works, the single cell cohorts from GSE89567, GSE84465, and the Chinese Glioma Genome Atlas (CGGA) datasets were used to analyze the key genes of macrophage. The bulk sequencing data from the Cancer Genome Atlas (TCGA) and CGGA datasets were respectively divided into the training set and validation set to test prognostic value of the key genes from single cell analysis. Results: The proportion of macrophage was not only significantly different between lower-grade glioma and high-grade glioma, but also so many different genes and cell functions remained among them in single cell analysis. Furthermore, based on univariate Cox regression, the Least Absolute Shrinkage and Selection Operator (LASSO) analysis and multivariate Cox regression, a predictive model were built. The risk score calculation formula was yielded as follows: Risk score = (0.11 × EXPMACC1) + (−0.31 × EXPOTUD1) + (−0.09 × EXPTCHH) + (0.26 × EXPADPRH) + (-0.40× EXPABCG2) + (0.21 × EXPPLBD1) + (0.12 × EXPANG) + (0.29 × EXPQPCT). The risk score was independently related to prognosis. Further, significant differences existed in immunological characteristics between the low- and high-risk score groups. What is more, mutation analysis found different genomic patterns associated with the risk score. Conclusion: This study further confirms that the proportion of macrophage infiltration is not only significantly different, but the function of them is also different. The signature, identified from the differentially expressed macrophage-related genes impacts poor prognosis and short overall survival and may act as therapeutic targets in the future.